Bahasa Indonesia Bahasa Inggris - Ananda Putri Norma Rahayu; Nurmalia Lusida (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
Adolescence is a transition of life from childhood to adulthood. The menstrual cycle is the period between the start of the last menstrual period and the start of a new period. Stress can affect the menstrual cycle in addition to stress which can affect the irregularity of the menstrual cycle, namely a person's nutritional status. The purpose of this study was to find out the relationship between stress levels and nutritional status with menstrual cycle irregularities in class XII young women at SMK Nusantara 02 Health Ciputat in 2022. This research was conducted in December 2022 using a cross-sectional design. Samples were taken using a total sampling technique of 70 respondents. Data analysis was performed using the Chi-Square Test and Simple Logistic Regression Test. The results of the bivariate test showed that there was no relationship between stress levels (p=0.404) and nutritional status (p=0.465) with irregular menstrual cycles in adolescents (p>0.05). Suggestions for adolescents to start paying attention to changes in the menstrual cycle regularly every month and start maintaining their weight by doing regular exercise and carrying out various activities to reduce their stress levels by playing with friends shopping, and using smart phones to access social media such as YouTube, Instagram and other social media.